Food profile of Yanomami indigenous children aged 6 to 59 months from the Brazilian Amazon, according to the degree of food processing: a cross-sectional study - Aline Oliveira dos Santos Moraes; Elma Izze da Silva Magalhães; Jesem Douglas Yamall Orellana; Giovanna Gatica-Domínguez; Paulo Augusto Ribeiro Neves; Paulo Cesar Basta; Juliana dos Santos Vaz (Cambridge University Press, 2023)
Abstract Objective: The current study aimed to characterise the food profile of Yanomami indigenous children according to the degree of food processing and its associated factors. Design: This is a cross-sectional study with Yanomami indigenous children aged 6 to 59 months. Socio-demographic, maternal and infant data were collected through a standardised questionnaire. The food profile was obtained by using a list of thirty-four foods to verify the child's consumption of these foods on the day preceding the interview. Foods were classified according to the degree of processing based on the NOVA system (in natura or minimally processed, processed culinary ingredients, processed and ultra-processed). In natura and minimally processed foods were subdivided into 'regional' and 'urban' foods. Poisson regression analysis was applied to estimate the associated factors according to the 90 % CI. Setting: Three villages (Auaris, Maturacá and Ariabú) in the Yanomami indigenous territory, in the Brazilian Amazon. Participants: In total, 251 Yanomami children aged 6 to 59 months were evaluated. Results: The prevalence of consumption of 'regional' and 'urban' in natura or minimally processed foods was 93 % and 56 %, respectively, and consumption of ultra-processed foods was 32 %. Ultra-processed food consumption was 11·6 times higher in children of Maturacá and 9·2 times higher in Ariabú when compared with the children of Auaris and 31 % lower in children who had mothers with shorter stature. Conclusion: Despite the high frequency of consumption of in natura and minimally processed foods, the consumption of ultra-processed foods was substantial and was associated with demographic and maternal factors in Yanomani indigenous children under 5 years of age.